Pore-Scale Modeling of Liquid Water Transport in Compressed Gas Diffusion Layer of Proton Exchange Membrane Fuel Cells Considering Fiber Anisotropy - Hao Wang; Guogang Yang; Shian Li; Qiuwan Shen; Yue Li; Renjie Wang (Membranes, 2023)
Water management of the gas diffusion layer (GDL) is crucial to the performance of proton exchange membrane fuel cells (PEMFCs). Appropriate water management ensures efficient transport of reactive gases and maintains wetting of the proton exchange membrane to enhance proton conduction. In this paper, a two-dimensional pseudo-potential multiphase lattice Boltzmann model is developed to study liquid water transport within the GDL. Liquid water transport from the GDL to the gas channel is the focus, and the effect of fiber anisotropy and compression on water management is evaluated. The results show that the fiber distribution approximately perpendicular to the rib reduces liquid water saturation within the GDL. Compression significantly changes the microstructure of the GDL under the ribs, which facilitates the formation of liquid water transport pathways under the gas channel, and the increase in the compression ratio leads to a decrease in liquid water saturation. The performed microstructure analysis and the pore-scale two-phase behavior simulation study comprise a promising technique for optimizing liquid water transport within the GDL.